Investigation of Structural, Spectral, and Dielectric Properties of CdSubstituted NiCoPr Nano Ferrites - Manzoor, Alina; Abubakar, Muhammad; Afzal, Amir Muhammad; Arshad, Muhammad Imran; Rasul, M. Nasir (Journal of Materials and Physical Sciences, 2021)
The effect of cadmium ions on the structural, spectral, and dielectric properties of Pr doped Ni0.4Co0.6-xCdxFe1.95Pr0.05O4 ferrites synthesized by the self-ignited sol-gel process is investigated in the present work. The addition of cadmium ions in place of cobalt ions resulted in an increase in the lattice constant. X-ray diffraction experiment revealed the single-phase spinel structure. The obtained average crystallite size is ranging from 20 - 30 nm. By increasing the substitution of cadmium ions, the dielectric constant, dielectric loss (tan ?) and impedance are noted to increase. SEM study found the spherical grain morphology with some degree of agglomeration. The existence of pores, the sintering process, and the magnetic activity of the particles may be responsible for nanosized particles with a homogeneous particle size distribution. Raman spectra revealed a slight shifting in Raman modes with cadmium addition which may be attributed to the strain produced due to the presence of larger cadmium ions at the Fe3+ site.